Evaluation of the masking ability, marginal adaptation, and fracture resistance of screw-retained lithium disilicate implant-supported crowns cemented to titanium bases versus preparable abutments - Ahmad Waled Mohamad Kordi; Abdallah Ibrahim Salman; Nayrouz Adel Metwally; Mohamed Moataz Khamis (BMC, 2023)
Abstract Background Straight preparable abutments and titanium bases (ti-base) can be used to support single-unit screw-retained lithium disilicate implant-supported restorations. The choice between using both abutments depends on many factors. The purpose of this in vitro study was to compare the masking ability, marginal adaptation, and fracture resistance of screw-retained lithium disilicate implant-supported crowns cemented to straight preparable abutments and ti-bases. Methods Twenty laboratory implant analogs (Straumann Bone Level; Straumann AG) were randomly divided into 2 groups (n = 10 each) according to the type of the abutment used. Preparable abutment group and ti-base group. Lithium disilicate crowns were used to restore the specimens. All specimens were subjected to thermocycling (from 5 to 55 °C for 2000 cycles) followed by cyclic loading (120 000 cycles). The vertical marginal gap between the abutment finish line and the most apical part of the crown was measured in (µm) by using a stereomicroscope after cementation and after thermocycling and cyclic loading. A spectrophotometer was used to evaluate the masking ability of the specimens after cementation. The load required to fracture the crowns was measured in Newtons (N) by using a universal testing machine after thermocycling and cyclic loading. The Shapiro-Wilk test of normality was used. The appropriate statistical test was used. Results Regarding the masking ability, the color difference (∆E) showed no statistically significant difference between the ti-base group (2.6 ± 0.2) and the preparable abutment group (2.6 ± 0.3) (P = .888). The average of the microgap values (µm) was greater in ti-basegroup after cementation (13.9 ± 9.2) than preparable group (7.63 ± 1.78) with no statistically significant difference between the 2 groups (P = .49). After cyclic loading and thermocycling, the average microgap values (µm) was significantly greater in the ti base group (21.3 ± 7.4) than in preparable group (13.3 ± 1.5) (P = .02). The load required to fracture the specimens was greater in the preparable group (1671.5 ± 143.8) than in the ti-base group (1550.2 ± 157.5) with no statistically significant difference between the 2 groups (P = .089). Conclusion The abutments used in the present study did not compromise the masking ability of the screw-retained lithium disilicate implant supported crowns. Moreover, the crowns cemented to preparable abutments had better marginal adaptation and higher fracture resistance when compared to those cemented to ti-bases. Clinical implications Straight preparable abutments are considered as an alternative to the ti-bases when restoring single screw-retained lithium disilicate implant-supported crowns with comparable fracture resistance, marginal adaptation, and masking ability.